(untitled) (Journal of the College of Languages (JCL), 2009)
Native speakers of English from different parts of the world have different accents,but the differences of accents are mainly the result of differences in the sound of vowels and consonants . The actual use of all these sounds in combination leads the speaker to produce a number of segments which only appear on the production level and realized on the perceptual one . RP pronunciation represents the teachable variety in all Iraqi universities because it is the most acceptable and understandable accent all over the world and not only in South East London ..The structure of the English syllable in RP pronunciation is influenced by the appearance of certain allophones especially aspiration and glottalization which change the form of CV in RP pronunciation.